LEGALITY OF IJAB-KABUL IN ONLINE MARRIAGE FROM MAQASHID SHARIA PERSPECTIVE - Candra, Anton Afrizal; Raihanah, Raihanah Abdullah (UIR Law Review, 2025)
Technological advances and developments that are so rapidly giving birth and giving rise to various problems in family law, such as marriages carried out via online. In most people's view, marriage is a very sacred matter and according to prevailing customs, marriage is carried out directly. At certain times, circumstances demand that it is not in line with the custom of the marriage being carried out, such as very long distances or circumstances that make it impossible to gather during the COVID-19 pandemic. The validity of a marriage is determined by the perfection of the pillars and the conditions for a valid marriage. The existence of a prospective husband, prospective wife, guardian, 2 witnesses and a marriage agreement are the pillars of marriage, and must be carried out in one assembly, according to the consent and acceptance and the guardian does not depend on the terms and times in the future. Interpreting the meaning of an assembly, whether in the same place or at the same time, there are also differences of opinion among Islamic jurists. These differences of opinion lead to differences in establishing marriage laws via online. The first group stated that it was illegal due to caution in matters of the dignity and honor of women which led to legal consequences. The second group stated that it was permissible because they did not have a fundamental difference, only different locations and places of marriage.